Analisis Layanan Sistem Informasi Akademik Perguruan Tinggi Berbasiskan Fuzzy Service Quality - I.G.P. Asto Buditjahjanto (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2020)
A higher education institution as an organization that offers academic information system services must be able to analyze their academic information system services. To analyze academic information system services, higher education institution must be able to measure the gap between perceptions and expectations of the users. The analysis is carried out on the five dimensions of service quality (Servqual) and its indicators so that each gap can be identified whether positive or negative. Fuzzy service quality method is used in this study because it can eliminate inconsistencies, uncertainties, and inadequacy in assessing an existing problem in academic information system. The results show that all gap values in the service quality dimension show negative signs. This shows that the services provided do not meet user's expectations. Therefore, it needs improvement for those services. The highest gap in the dimension of service quality is reliability at -1.010, followed by responsiveness at -0.906, assurance at -0.831, empathy at -0.703, and tangibility at -0.685.